Застосування методу «дерева рішень» для побудови системи встановлення діагнозу - Басюк, Тарас; Дуб’як, Ірина (Видавництво Львівської політехніки, 2017)
This article is dedicated to description of applying features of the “decision tree” method in a process of making a diagnosis. The current state of subject area studied has been analyzed, the main problem areas have been defined and functions of the designed diagnostic system have been determined. Analysis of the task solutions showed that in this case the effective one is the “decision tree” method, in particular classification tree – the subspecies according to the type of predicted indicator. The decision tree has been built and the conclusions about the feasibility of its application have been made.
Keywords: діагностування; симптоми; захворювання; дерево рішень